SISTEM PELAYANAN BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA SAMARINDA - Sarwo Eddy Wibowo dan Aidar Erika Toding Pali (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
Baznas as a trusted amil zakat body because it is centralized and regulated by the government of the Republic of Indonesia and has a legal basis, namely Law No. 23 of 2011 and has standardization and professionalism. This has triggered Baznas to continue to implement a good prime service system, especially in managing and distributing zakat. This is implemented through a zakat service program that seeks to ensure that zakat can be collected from benefactors and muzzaki in a professional and prime manner. This is what muzzaki demands besides good service as well as professional governance. This type of research uses a qualitative approach.  The subject of this research is the National Zakat Agency. Meanwhile, the object of research is the service system. Sources of data obtained by researchers are primary data in the form of interviews, observation and documentation and secondary data through library sources. The results of the research obtained are that the Samarinda City Baznas service system has a series of strategies and processes in zakat management starting from the process of zakat, infaq and sadaqah services, the collection and collection process, distribution programs, and improvement of human resources. The service system of Baznas Kota Samarinda is in accordance with the indicators of excellent service quality, namely transparency, accountability, conditionality, participation, equality of rights, and balance of rights and obligations